2019
DOI: 10.7717/peerj.7630
|View full text |Cite
|
Sign up to set email alerts
|

Measuring body dimensions of leopards (Panthera pardus) from camera trap photographs

Abstract: Measurement of body dimensions of carnivores usually requires the chemical immobilization of subjects. This process can be dangerous, costly and potentially harmful to the target individuals. Development of an alternative, inexpensive, and non-invasive method therefore warrants attention. The objective of this study was to test whether it is possible to obtain accurate measurements of body dimensions of leopards from camera trap photographs. A total of 10 leopards (Panthera pardus) were captured and collared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…This report is, in fact, the first study combining camera trapping and a photogrammetry technique to estimate morphological traits of animals. However, it is important to note that their method may be only applicable to marked carnivores that readily take baits and can climb up the leading pole (Tarugara et al, 2019). Instead, the method described here further explored the feasibility to measure shoulder height and maybe other body dimensions, on free-ranging animals by camera traps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This report is, in fact, the first study combining camera trapping and a photogrammetry technique to estimate morphological traits of animals. However, it is important to note that their method may be only applicable to marked carnivores that readily take baits and can climb up the leading pole (Tarugara et al, 2019). Instead, the method described here further explored the feasibility to measure shoulder height and maybe other body dimensions, on free-ranging animals by camera traps.…”
Section: Discussionmentioning
confidence: 99%
“…Willisch et al (2013) suggested that it might be well worth setting camera traps and scaling objects to automatically take photographs for estimating the horn annuli of Alpine ibex (Capra ibex). Although Tarugara et al (2019) tested a method to measure body dimensions of leopards from photographs collected during a baited camera-trapping survey, to date, no study has further demonstrated the utility of camera trapping as a tool for photogrammetric trait estimation. Here, based on practical experience in fieldwork, we combine these two techniques and present a new approach that allows for robust estimation of the target animals' shoulder height under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Suitable images were defined as those taken of either the right or left lateral side of each painted dog at a right angle (i.e., perpendicular), with the axilla, front leg angle, belly, and sacroiliac process all visible and all four feet aligned on the ground (X-X’ line; Fig 2 ). The use of ratios and standardisation of the type of photos allowed for analysis enabled us to obtain images from sources “outside” our study as it has been noted that body size and distance from the camera do not influence the accuracy of morphometric measurements [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…The use of an algorithm approach (as offered here) provides a structured process for obtaining belly scores based on multiple structural regions of the body on individuals in photographs, introducing inherently less interobserver bias and variability [ 13 ], particularly with the assistance of software measuring tools. For example, photogrammetric measurements were reliably used to measure painted dog cranial asymmetry [ 31 ] and morphometric differences in painted dog populations across Africa [ 17 ], as well as life stages of marbled salamanders ( Ambystoma opacum ) [ 32 ] and body dimensions (posture dependent) in primates [ 33 ] and leopards [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Tarugara et al. [14] used steel nails driven 20 cm apart into the underside of the leading pole as a scaling standard and in this way, leopards photographed from each sampling station could be measured ( Fig. 5 ).…”
Section: Advantages Of the Bct Methodsmentioning
confidence: 99%